Improvements in the manufacture of benzoic acid obtained by catalytic oxidation of toluene - João Guilherme Rocha Poço; Rodrigo Cella; Silas Derenzo (The Journal of Engineering and Exact Sciences)
This study investigates improvements in benzoic acid production through the catalytic oxidation of toluene with cobalt octoate. The oxidation process, which occurs under controlled conditions with temperatures ranging from 130 °C to 165 °C, typically results in a conversion rate of 50% toluene with a selectivity of 80% over benzoic acid. However, various by-products such as benzyl alcohol, benzaldehyde, and benzyl benzoate are also formed, which reduces the overall yield. The work identifies methods to minimize these byproducts, particularly benzyl benzoate, which forms in the distillation column. One strategy investigated involved using additives to inhibit the esterification reaction that produces benzyl benzoate, aiming to improve the selectivity of the oxidation process. Experimental results show that maintaining reaction temperatures between 135 °C and 145 °C in combination with using sodium benzoate as an additive effectively reduces the formation of benzyl benzoate and increases the yield of benzoic acid. Furthermore, increasing the O2/toluene ratio increases the oxidation efficiency.